ANALISIS PENGEMBANGAN PEGAWAI PADA DINAS PARIWISATA, PEMUDA DAN OLAHRAGA KABUPATEN NIAS - Waruwu, Vikar Fisratna; Ndraha, Ayler B.; Buulolo, Nanny Artatina; Halawa, Odaligoziduhu (FEB Universitas Sam Ratulangi Manado, 2024)
The need to obtain superior and professional human resources is highly expected by every organization. So much human resource development funding is spent for this purpose, but it often results in disappointment. In achieving its goals, organizations strive to create human resources who are reliable and have the ability by opening the mindset of human resources in the organization. Employee development is an integral part of talent management. Skills refer to the combination of knowledge, attitudes and behaviors that enable a person to succeed in a particular job or task. Employee development involves a series of efforts designed to improve individual abilities, knowledge and skills so that they can achieve better performance and be more relevant to job demands. By integrating talent management with employee development, organizations can create an environment where individuals feel valued, have opportunities to grow, and make greater contributions to the organization's success. This research used qualitative methods with informants as many as 8 employees at the Nias Regency Tourism, Youth and Sports Office. The research results show that the employee development program is designed to improve the skills, knowledge and abilities of employees so that they can make a greater contribution to their duties and responsibilities in carrying out their assigned tasks. With employee development carried out at the Nias Regency Tourism, Youth and Sports Department, employees experience increased skills, work motivation, work enthusiasm, job or position promotions as well as improving employee leadership, competence and performance through training activities and providing opportunities for employees to program further education.